1984
DOI: 10.1029/ja089ia12p11053
|View full text |Cite
|
Sign up to set email alerts
|

EUV airglow during active solar conditions: 2. Emission between 530 and 930 Å

Abstract: Daytime airglow spectra between 530 and 930 ,• were obtained at --4 ,• resolution from a rocket launch at White Sands, New Mexico, June 27, 1980. Portions of the spectrum were observed in second order at --2,• resolution. The higher resolution of the present data confirms our previous identification of OII transitions and resolves the identification of OII emission at 537-539 ,• as due to both a doublet and a quartet component. For the case of viewing at 90 ø to the zenith between 196 and 242 km --1/3 of the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
(6 reference statements)
1
22
0
Order By: Relevance
“…Several VUV emission lines of O + + have indeed been observed in aurorae or diurnal high-resolution emission spectra at 50.8, 52.6 and 70.3 nm. 12,13 The emissions at 495.8911 nm and 500.6843 nm have just recently been identified in VLT UVES spectra acquired in 2003. 36 The emissions near 166-167 nm may be identified in a spectrum acquired with the HUT telescope (see Fig.…”
Section: Spectroscopy and Remote Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several VUV emission lines of O + + have indeed been observed in aurorae or diurnal high-resolution emission spectra at 50.8, 52.6 and 70.3 nm. 12,13 The emissions at 495.8911 nm and 500.6843 nm have just recently been identified in VLT UVES spectra acquired in 2003. 36 The emissions near 166-167 nm may be identified in a spectrum acquired with the HUT telescope (see Fig.…”
Section: Spectroscopy and Remote Sensingmentioning
confidence: 99%
“…Moreover, as their detection both by remote or in situ methods is a real challenge, there was no way to check their existence and measure their density. However some satellite measurements have shown that atomic doublycharged ions are present in the ionospheres of the Earth, [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Venus 17,18 and Io. [19][20][21] Molecular doubly-charged ions have not been detected in any ionosphere so far, even if they…”
Section: Introductionmentioning
confidence: 99%
“…Long‐term sensor trending indicates that normal aging and contamination would have reduced the overall EUVS sensitivity by less than 2% from the preflight calibration value for these measurements that were collected less than 3 weeks after sensor turn‐on [ Stephan et al , 2011]. A spectral model was created that convolved the RAIDS EUVS line shape with emissions measured by Gentieu et al [1984], including the bright O II 83.4 nm feature, the He I 58.4 nm line, and several O II emissions including the 61.7 nm feature presented in this paper. Additionally, an instrumental background component, representing primarily light scattered into the sensor aperture from surrounding ISS structures, was derived from measured, featureless, high‐altitude and nighttime spectra.…”
Section: Raids Observationsmentioning
confidence: 99%
“…At extreme ultraviolet (EUV) wavelengths shorter than 100 nm, where emissions directly reflect solar photoionization processes in the upper atmosphere, observations of airglow features provide a unique opportunity for remote sensing of the global ionosphere. Under exposure to solar EUV, direct photoionization of atomic oxygen leads to O II emission lines that pervade the terrestrial EUV airglow spectrum between 60 and 85 nm [ Gentieu et al , 1984]. The brightest and most promising of these emissions for ionospheric remote sensing is the O II 83.4 nm triplet (2 p 4 4 P → 2 p 3 4 S ) [ Meier , 1991].…”
Section: Introductionmentioning
confidence: 99%
“…Rocket observations of the extreme ultraviolet (EUV) and far ultraviolet (FUV) daytime airglow were made during moderate solar activity on January 9, 1978 [Gentieu et al, 1979;Feldman et al, 1981]. The EUV/FUV spectrum was measured again during high solar activity on June 27, 1980 [Christensen et al, 1982;Gentieu et al, 1984;Eastes et al, 1985;Meier et al, 1985]. In this report we present the altitude profile of the 834-•_ emission from the 1980 rocket flight.…”
Section: Introductionmentioning
confidence: 99%